PENERAPAN MANAJEMEN STRATEGIK MENGGUANAKAN ANALISIS SWOT UNTUK MENINGKATKAN DAYA SAING PEMASARAN PADA MU GUNG HWA SUPERMARKET - Devi Apriliana; Nazwa Octsalsabilla; Fazirah Faiz (Jurnal Ilmiah Akuntansi, 2026)
The retail industry has become increasingly competitive, accompanied by changes in consumer behavior toward digital shopping. As a retailer specializing in Korean products, Mu Gung Hwa Supermarket needs to implement strategic management to adapt to changes in the business environment and maintain its marketing competitiveness.   This study aims to analyze the implementation of strategic management using SWOT analysis to improve the marketing competitiveness of Mu Gung Hwa Supermarket. The research employed a descriptive qualitative approach using SWOT analysis. Data were collected through observations, interviews, and a review of relevant literature.   The results show that Mu Gung Hwa Supermarket's strengths include a comprehensive range of Korean products, high-quality customer service, and the utilization of digital media. However, the company also faces several weaknesses, including relatively high prices for imported products, a limited number of branches, and digital promotional activities that have not yet been optimized. Opportunities arise from the growing public interest in Korean culture, while the main threats come from competition with modern retail businesses and online shopping platforms.   Based on the SWOT analysis, the company should strengthen its digital marketing strategy, improve service quality, and develop more innovative promotional programs to capitalize on market opportunities and enhance its marketing competitiveness sustainably.